Application of Blog For Media Learning of Online Marketing courses/ Penerapan Blog Sebagai Media Pembelajaran Mata Pelajaran Pemasaran Online - Doni Erfianto; Wening Patmi Rahayu; Djoko Dwi Kusumajanto (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2015)
This study aims to: 1) describe the implementation of blog as a learning medium for online marketing subject; 2) determine students' response on the implementation of blog as a learning medium for online marketing subject; and 3) know the advantages and disadvantages after the implementation the implementation of blog as a learning medium for online marketing subject. This research is a qualitative descriptive research. Data that were taken for this study is based on the observation sheet and questionnaire. In addition, the data sources that are taken are 26 tenth grade students of Marketing 2 at SMKN 1 Probolinggo. The research finding showed that: 1) the implementation of a blog can help students to learn online marketing materials; 2) the results of the questionnaire showed that students responded positively on the implementation of blogs as a learning medium; and 3) the advantages and disadvantages after the implementation of blogs as a learning medium are: a) advantages: teachers can operate a blog, students can be more active in the learning activities and creating innovative and creative learning; b) dissadvantages: there is one student who did not like the virtual world and if there is a blackout, the teaching and learning activities is disrupted.Abstrak: Penelitian ini bertujuan untuk 1) mendeskripsikan penerapan blog sebagai media pembelajaran mata pelajaran pemasaran online, 2) mengetahui respon siswa terhadap penerapan blog sebagai media pembelajaran mata pelajaran pemasaran online, 3) mengetahui kelebihan dan kekurangan setelah penerapan blog sebagai media pembelajaran mata pelajaran pemasaran online. Jenis penelitian ini adalah deskriptif kualitatif. Data yang diambil untuk penelitian ini berdasarkan pada lembar observasi dan angket. Sedangkan sumber data yang diambil yaitu 26 siswa kelas X PMS 2 di SMKN 1 Probolinggo. Hasil penelitian menunjukkan bahwa 1) penerapan blog dapat membantu siswa dalam belajar materi pemasaran online, 2) hasil angket menunjukkan bahwa siswa memberikan respon yang positif terhadap penerapan blog sebagai media pembelajaran, 3) kelebihan dan kekurangan setelah penerapan blog sebagai media pembelajaran a) kelebihan: guru dapat mengoperasikan blog, siswa lebih aktif dalam kegiatan pembelajaran serta pembelajaran menjadi inovatif dan kreatif b) kekurangan: ada satu siswa yang tidak suka dengan dunia maya dan apabila listrik mati kegiatan belajar mengajar terganggu.